2021
DOI: 10.2337/dc21-0342
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Type 1 Diabetes May Be Underestimated in the Chinese Population: Evidence From 21.7 Million People Between 2007 and 2017

Abstract: OBJECTIVE Previous reports of the annual incidence of type 1 diabetes (T1D) in China were conducted using retrospective hospital cases, which may not reflect the reality. This longitudinal study estimated T1D incidence in a Chinese population of 21.7 million from 2007 to 2017. RESEARCH DESIGN AND METHODS A population-based registry of T1D was performed by the Beijing Municipal Health Commission Information Center. Annual inci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 36 publications
1
20
2
Order By: Relevance
“…The peak period of disease onset was in school-aged children (aged 5 to <10 years, 38.7%), which is similar to the report of the SEARCH (SEARCH for Diabetes in Youth) study in the United States ( 21 ). Women had a slightly higher morbidity of T1DM, consistent with the previous findings ( 4 ), which may be one of the features of childhood T1DM in China. Although obesity is associated with the increasing presentation of T1DM for a potentially excess β-cell stress ( 22 , 23 ), the patients were rarely obese at diagnosis in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The peak period of disease onset was in school-aged children (aged 5 to <10 years, 38.7%), which is similar to the report of the SEARCH (SEARCH for Diabetes in Youth) study in the United States ( 21 ). Women had a slightly higher morbidity of T1DM, consistent with the previous findings ( 4 ), which may be one of the features of childhood T1DM in China. Although obesity is associated with the increasing presentation of T1DM for a potentially excess β-cell stress ( 22 , 23 ), the patients were rarely obese at diagnosis in our study.…”
Section: Discussionsupporting
confidence: 91%
“…The global average increase in incidence has been 3–4% per year over the past decades, with an especially steeper rise in low-incidence countries ( 3 ). The incidence of T1DM remains unstable in China, a longitudinal population-based registry study showed that it significantly increased from 2.72/100,000 in 2007 to 3.60/100,000 in 2017 ( 4 ). One nationwide registry study based on multiple centers showed that the incidence of T1DM in children aged between 0 and 14 years was 1.9/100,000 ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…A population based study has shown that China has 13,000 newly diagnosed type 1 diabetes mellitus (T1DM) cases every year despite a low incidence rate of 1.01/100,000 person-years from 2010 to 2013 ( 1 ). A recent longitudinal study has demonstrated that T1DM incidence increased from 2.72 to 3.60/100,000 person-years in a Chinese population from 2007 to 2017 ( 2 ). The aims of T1DM management are to avoid acute diabetic complications and prevent or delay chronic diabetic complications and mortality as well as maintain quality of life ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…More than 500,000 new cases are diagnosed each year and 22 million people are estimated to be living with T1DM worldwide [ 3 ]. In China, the incidence of T1DM is lower than in Western countries but has been rising steadily over the past decades [ 4 6 ]. According to a recent population-based study, the annual incidence of T1DM per 100,000 in China increased from 2.72 in 2007 to 3.60 in 2017 [ 6 ], which is considerably higher than earlier estimates [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In China, the incidence of T1DM is lower than in Western countries but has been rising steadily over the past decades [ 4 6 ]. According to a recent population-based study, the annual incidence of T1DM per 100,000 in China increased from 2.72 in 2007 to 3.60 in 2017 [ 6 ], which is considerably higher than earlier estimates [ 7 ]. The economic burden of T1DM is substantial, with costs per patient that exceed those of type 2 diabetes mellitus (T2DM) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%